Botryosphaeriaceae associated with Tectona grandis (teak) in Northern Thailand - Doilom, Mingkwan; Shuttleworth, Lucas A.; Roux, Jolanda; Chukeatirote, Ekachai; Hyde, Kevin D. (Phytotaxa, 2015)
Tectona grandis (teak) is one of the most important economic timbers worldwide. Limited studies exist on the potential pathogens of these trees. Fungi in the Botryosphaeriaceae are cosmopolitan opportunistic pathogens, endophytes and saprobes of numerous hosts. Both symptomatic and asymptomatic branch and stem sections, as well as leaves were collected from T. grandis in plantations and forests in four provinces of northern Thailand with the aim of identifying species of Botryosphaeriaceae associated with these trees. Morphology and multi-locus phylogenies (ITS, TEF1-α, β-tubulin) were used to identify the Botryosphaeriaceae species. Six species from four different genera were found on T. grandis in Northern Thailand. These included Dothiorella tectonae sp. nov., Lasiodiplodia brasiliense, L. pseudotheobromae, L. theobromae, Pseudofusicoccum adansoniae and Sphaeropsis eucalypticola. Dothiorella tectonae is introduced here as a novel species and compared with other species in the genus. Dothiorella tectonae, L. brasiliense, L. pseudotheobromae, L. theobromae, P. adansoniae and S. eucalypticola are first reports for T. grandis in Thailand. Variations in morphology between descriptions of previously described species and that obtained in this study are described to facilitate future identification of species.